Sexually transmitted infections related care-seeking behavior and associated factors among reproductive age women in East Africa: a multilevel analysis of demographic and health surveys - Ever Siyoum Shewarega; Elsa Awoke Fentie; Desale Bihonegn Asmamaw; Wubshet Debebe Negash; Samrawit Mihret Fetene; Rediet Eristu Teklu; Fantu Mamo Aragaw; Tewodros Getaneh Alemu; Habitu Birhan Eshetu; Daniel Gashaneh Belay (BMC Public Health, 2022)
Abstract Background Sexually transmitted infections are serious global public health issue, and their consequences contribute significantly to population morbidity and mortality, especially in Sub-Saharan Africa. However, there is limited information about the sexually transmitted infections related care-seeking behavior in East Africa. Therefore, this study aimed to assess the pooled prevalence of sexually transmitted infections related care-seeking behavior, and associated factors among reproductive-age women in East Africa using the recent Demographic and Health Survey. Methods This study was based on recent Demographic and Health Survey of 8 East African countries from 2008/09 to 2018/2019. A total weighted sample of 12,004 reproductive-age women who reported sexually transmitted infections or symptoms of sexually transmitted infections in the last 12 months wereincluded. A multi-level mixed-effect logistic regression model was used and a P-value of < 0.05 was considered a statistically significant level for identification of individual and community level factors and AOR with a 95% l CI was computed. Result The overall prevalence of sexually transmitted infections related care-seeking behavior among reproductive-age women in East African countries was 54.14% [95% CI: 53.25%, 55.03%]. In multilevel analysis: being age 25–34 [AOR = 1.27 95%CI: 1.15–1.41], 35–49 [AOR = 1.26 95%CI: 1.13–1.41], women who attained secondary or above education [AOR = 1.27, 95% CI: 1.09, 1.47], being in rich household [AOR = 1.27, 95% CI 1.14, 1.41], women who were currently pregnant [AOR = 1.29, 95% CI 1.13, 1.47], who had been tested for HIV [AOR = 1.99, 95% CI 1.70, 2.33], women who had one and more than one sexual partner [AOR = 1.18, 95% CI 1.05, 1.34], women who lived in urban area [AOR = 1.16, 95% CI: 1.03, 1.31] and who perceived distance from the health facility was not a big problem was [AOR = 1.13, 95% CI 1.04, 1.23] were significantly associated with sexually transmitted infections related care-seeking behavior. Conclusion sexually transmitted infections related care-seeking behavior is relatively low as compared with other studies.. This study revealed that individual-level variables such as women's age, educational status, household wealth index, pregnancy status, ever been tested for HIV, number of sexual partners, and community-level variables such as residence and distance from a health facility were associated with sexually transmitted infections related care-seeking behavior. Therefore, public health interventions targeting uneducated women, poor households, and adolescents, as well as improving counseling and awareness creation during HIV/AIDS testing and Antenatal care visits, are vital to improving sexually transmitted infections care seeking behavior.